Transformasi Intelektual dan Kultural: Perkembangan Islam Pasca Serangan Mongol - Haif, Abu; Mahfudah, Rifkatul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study examines the intellectual and cultural transformation in the development of Islam following the Mongol invasion in the 13th century. The Mongol invasion, which destroyed many centers of Islamic civilization such as Baghdad, triggered a significant phase of reconstruction and adaptation in the Islamic world. The Mongol rulers who later embraced Islam played a crucial role in supporting the rebuilding of the destroyed cities and establishing new centers of learning. This study employs the Library Research method. It demonstrates how Islam was able to adapt and thrive despite facing great challenges. These findings highlight the ability of Islamic civilization to recover from destruction, generate innovation, and expand its intellectual and cultural heritage. This research contributes to a deeper understanding of the dynamics of adaptation and revitalization in the history of Islamic civilization.